Building a Parent Iridabenzene Structure from Acetylene and Dichloromethane on an Iridium Center1. Issue 38 (9th August 2013) - Vivancos, Ángela; Paneque, Margarita; Poveda, Manuel L.; Álvarez, Eleuterio
<x xml:space="preserve">Abstract</x> Parenthood: The reaction of [TpIr(C2H4)2] (1) (Tp=hydrotris(pyrazolyl)borate) with acetylene in CH2Cl2 affords a 1:1 mixture of the "parent" metallabenzene 2 (that is, all the ring carbon centers are CH units) and the β‐Cl substituted vinyl species 3. Generation of 2 is by the coupling of an iridacyclopentadiene (formed from two acetylene molecules at the Ir center) with the dichloromethane‐derived chlorocarbene ":C(H)Cl" and a subsequent α‐Cl elimination event.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>